The truth as aletheia, a tragic issue in Sophocles’ Oedipus Rex Iván (ALPHA. Journal of Arts, Literature and Philosophy, 2016)
To do justice we must know the truth. There are at least two types of justice: human and divine. Eventually the second one prevents errors of the first and amends uncontrollable human actions, imposing its power, order and punishment. This essay reflects on the theme of truth as aletheia, that is, as disclosure and remembrance in Sophocles' King Oedipus. In this drama, Apollo’s justice prevails and turns violent, because of unfortunate ―bloodshed‖ hidden and forgotten incidents. From the Delphi Oracle, the divine truth will emerge spilling blood from Thebas King’s eyes, demanding vengeance, without mercy for its players. The truth as aletheia is not only power, justice and punishment through the logos –this being what is relevant– but cry, blood and death, and tragedy.
Keywords: Aletheia; Truth; Deeds of blood; Tragedy; Violence; Excess